The role of inter-organizational innovation networks as change drivers in commercialization of disruptive technologies: The case of power-to-gas - Csedő, Zoltán; Zavarkó, Máté (International Journal of Sustainable Energy Planning and Management, 2020)
Power-to-gas (P2G) technology is an emerging disruptive solution for renewable electricity integration and energy storage. Two significant challenges of its commercialization are the perceived risks associated to its scalability and the cost-benefit ratio of P2G versus other innovative energy storage technologies. Its emerging regulatory and business environment significantly limit the accuracy of the financial models, as well. In our research we have examined how inter-organizational networks and innovation management could contribute to the commercialization of the technology in spite of the above mentioned challenges. We performed action research between 2016-2019 at Hungarian technology developer startup Power-to-Gas Hungary Kft. Our research results show that dyad-level open innovation led to a significant opportunity to make new steps towards the commercialization of the disruptive technology. Because of the exploitative characteristics of the market environment and emerging regulatory framework we identified significant needs for complementary resources that would drive successful commercialization. We found that inter-organizational P2G innovation networks and their role in shaping further innovation and the establishment of regulatory sandbox models might be essential to overcome barriers of commercialization of this disruptive technology.